Criteria of Classifying knowledge and Extent of their Usefulness in Slowing Problem of Academic Programming - Mohammed Shahid hamida Attaria (الدراسات الإسلامية, 2017)
The problem of classifying Knowledge engaged early Muslim scholars and fhilosohphers. many outstanding philosophers from Al-farabi, Sina to Imam Al- Khazali, Razi and Ibn Khaldun have addressed themselves to this problem and provided definite hierarchy in Knowledge from their perspective. This issue has been a familiar topic of discussion in the Muslim scholarly tradition long before the modern western academia. In recent teams, a number of writers have been explaining the classification of the various classical Muslim thinkers to familiariz their reader with their contribution. Wowever, little attention has been paid to comprehent the basic criteria adopted by these classical Masters in their respective classifications. This paper attempt to discern these criteria that guided the past thinkers and to explore the perspects of utilizing them to slowe the problems of the current academic programming and prioritzation. According to the writer, presents scholarship is settle unable to maintain calorie duty of vision about knowledge, its esential unity of source and ultimate objective. This confusion is evidencde by the dichotomy of This worldly, which still appears to influence some quarters.